Improving Performance in Securities Settlement Systems Using Multithreaded Transactions - Ramos, Jesus S (2009)
The aim of this research is to explore the performance improvements in Securities Settlement Systems (SSS) enabled by current trends in Enterprise Systems Technologies, placing particular emphasis in the implementation of the ‘delivery versus payment’ (DVP) specification using multiple concurrent threads. The motivation for this research lies on the omission of back-office finance by Computational Finance, and the general lack of academic work that brings together enterprise technologies with settlement systems. The timeliness of this research is further justified by the current focus on financial governance in the light of the 2008 financial crisis. The grounds for this study are laid by a literature review of the securities settlement process, its stakeholders and their relevant issues. Performance improvements are then explored by experimentation using a prototype system that processes DVPs in multiple threads, the results of which are then analyzed to derive key findings. The findings underline that, while there is a modest performance gain with the proposed multithreaded mechanism, there are technological limitations that prevent an effective use of multithreaded transactions that compromise the system’s compliance with the DVP specification. This study concludes that traditional enterprise infrastructures are unsuitable for processing DVPs using multiple threads, and two alternative technologies are suggested either to address or work around such limitation in future research.